Effectiveness and safety of cladribine in MS: Real-world experience from two tertiary centres. (February 2022) - Pfeuffer, Steffen; Rolfes, Leoni; Hackert, Jana; Kleinschnitz, Konstanze; Ruck, Tobias; Wiendl, Heinz; Klotz, Luisa; Kleinschnitz, Christoph; Meuth, Sven G; Pul, Refik
Background: Oral cladribine has been approved for the treatment of relapsing multiple sclerosis (MS) yet real-world evidence regarding its effectiveness and safety remains scarce. Objective: To evaluate efficacy and safety outcomes of MS patients following induction of cladribine. Methods: We evaluated our prospective cohort of cladribine-treated MS patients from two tertiary centres in Germany. Relapses, disability worsening and occurrence of new or enlarging T2-hyperintense magnetic resonance imaging (MRI) lesions were assessed as well as lymphocyte counts and herpes virus infections. Results: Among 270 patients treated with cladribine, we observed a profound reduction of both relapses and new or enlarging MRI lesions. Treatment appeared more efficacious, especially in patients without previous therapy or following platform substances. Patients switching from natalizumab were prone to re-emerging disease activity. Among patients following dimethyl fumarate pre-treatment, severe lymphopenia was common and associated with increased rates of herpes virus manifestations. Conclusion: Overall, we observed an efficacy and safety profile of cladribine consistent with data from the phase 3 clinical trial. However, patients switching from natalizumab experienced suboptimal disease control beyond rebound activity following cessation of natalizumab. Furthermore, dimethyl fumarate pre-treatment was associated with a profound risk of developing severe lymphopenia and subsequent herpes virus infections.